Biological fitness at middle-age is reduced in both very lean and obese males - Lipowicz, Anna (Polskie Towarzystwo Antropologiczne, 2003)
It is well-documented fact that the relationship between body weight and premature mortality is not linear. Very often it is described as J- or U-shaped. There is solid evidence for strong relationships in adults between obesity (as defined by high values of the body mass index, BMI), mortality, hypertension, cardiovascular disease, stroke, and non-insulin dependent diabetes. However, the opposite end of the BMI distribution (leanness) remains an area of controversy among European populations. Many authors have indicated that leanness elevates the risk of premature mortality, although to a lesse degree than obesity. The aim of this sudy is to examine whether abnormalities in blood pressure and lung function occur more frequently at both extremes of the BMI distribution than in its middle range.
Keywords: blood pressure; respiratory indices; J-shaped distribution; BMI